Knockout of the lysosomal membrane protein, LAMP2C, improves transient gene expression in HEK293 cells via increased intracellular plasmid availability - Kim, Dongwoo; Kim, Seul Mi; Lee, Jaejin; Kim, Jiwon; Lee, Jae Seong (Biotechnology Journal, 2024)
Plasmid-based transfection can be used in many applications such as transient gene expression (TGE)-based therapeutic protein production. These applications preferentially require maximization of intracellular plasmid availability. Here, we applied a lysosome engineering approach to alleviate lysosome-mediated nucleic acid degradation and enhance the TGE in mammalian cells. By knocking out the lysosomal membrane protein LAMP2C, which is known to be the main player in RNautophagy/DNautophagy (RDA), we significantly improved transient fluorescent protein expression in HEK293 cells by improving the retention rate of transfected plasmids; however, this effect was not observed in CHO cells. Additional knockout of a lysosomal membrane transporter and another RDA player, SIDT2, was ineffective, regardless of the presence of LAMP2C. LAMP2C knockout enhanced TGE-based mAb production in HEK293 cells by up to 2.82-fold increase in specific mAb productivity. Taken together, these results demonstrate that HEK293 cells can be engineered to improve the usage of the transfected plasmid via knockout of the lysosomal membrane protein LAMP2C and provide efficient host cells in TGE systems for therapeutic protein production.
Keywords: HEK cell; HEK293 cells; Knockout; LAMP2C; Lysosomal membrane protein; Lysosomal membranes; Membrane proteins; Plasmid degradation transient gene expression; Therapeutic protein; Transient gene expressions; Animals; Cricetinae; Cricetulus; Gene Expression; HEK293 Cells; Humans; Lysosomal Membrane Proteins; Nucleotide Transport Proteins; Plasmids; Transfection; HEK cells; knockout; LAMP2C; lysosomal membrane protein; plasmid degradation transient gene expression